MEANINGS EXPRESSED BY SILENCE AND INTONATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
It is well known that verbal communication differs from the simple realization of linguistic possibilities in a certain material form. Verbal communication is situational, so its forms and expressiveness are multifaceted.Currently, in Uzbek linguistics, cognitive linguistics is a new direction of research that determines the cognitive characteristics of linguistic units. Based on the commonality of the national language and national thinking, the study of the cognitive, expressive, accumulative aspects of each language event has become the main task of this direction.The article deals with verbal (synonymy, gradonyms, antonyms, paraphrase, metaphor, metonymy, synecdoche, irony, phraseologies, euphemisms, etc.) and non-verbal (tone, silence) units that serve to identify medical euphemistic meanings of a language as the means of implementing linguistic pragmatics are analyzed .